Prevalence of anaemia among the male population aged 60 years and above in rural area of Paschim Medinipur, West Bengal, India (Health Renaissance, 2013)
Background: Anaemia is one of the most common public health problems of older population especially in developing countries. Objective: To determine the prevalence and type of anaemia present among the older people in rural area of Paschim Medinipur, West Bengal. Methods: A cross-sectional study was undertaken on 544 older male, Subject aged 60 to 84 years from Paschim Medinipur, West Bengal. Personal details were collected in each case, after which height, weight, body mass index (BMI) and blood haemoglobin level were measured according to the standard protocol. Anaemia was classified as per the World Health Organisation (WHO) grading criteria.Results: The overall prevalence of anaemia among the older male was 89.52%. The majority (256) (47.05%) showed mild anaemia, while moderate anaemia was recorded in 212 (38.97%) and 19 (3.49%) subjects, had severe anaemia. The prevalence of anaemia was more (65.62%) in individuals, having low BMI than normal. Conclusion: The results showed high frequency of anemia in the studied population. There is a need for immediate nutritional intervention programs to be implemented among the rural older male subjects. Health Renaissance, January-April 2013; Vol. 11 No.1; 23-26 DOI: http://dx.doi.org/10.3126/hren.v11i1.7597